Mr. Monk is a mess [large type] : a novel - Goldberg, Lee, 1962- (Monk series (New York, N.Y.), 2012)
When Adrian Monk and Natalie come home to San Francisco after working as cops in New Jersey, Natalie discovers somebody has been sleeping in her bed, but this Goldilocks is not asleep--she's dead!